1996
DOI: 10.1046/j.1365-2648.1996.12910.x
|View full text |Cite
|
Sign up to set email alerts
|

'Knowing the patient': a review of research on an emerging concept

Abstract: Knowing the patient is an important concept emerging from recent studies of nursing practice. The concept is relevant to therapeutic decision-making. Also, knowing the patient actualizes a cherished value in nursing: the treatment of persons as unique individuals. Investigators described that knowing the patient comprises two components: the nurse's understanding of the patient and the selection of individualized interventions. In addition, the nurse's experience with caring for patients, chronological time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 10 publications
7
117
0
4
Order By: Relevance
“…[29][30][31] This study suggests that CP/ CPSs "know" and care for patients in a way that is distinct from nursing. For example, in disease-state management, CPs/CPSs see the same patients over and over again in ACC but also in diabetes clinics and hypertension clinics, among many others.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[29][30][31] This study suggests that CP/ CPSs "know" and care for patients in a way that is distinct from nursing. For example, in disease-state management, CPs/CPSs see the same patients over and over again in ACC but also in diabetes clinics and hypertension clinics, among many others.…”
Section: Discussionmentioning
confidence: 85%
“…This study identified that long-term relationships help CPs/CPSs know the patient as a person and that this knowing leads pharmacists to make individualistic, personalized interventions. 29,30 This is especially apparent in the strategy categorized as identifying a patient's unmet needs (e.g., when patients ask directly for help), or there is an indirect expression of need (e.g., the loss of cognitive function identified by the CP/ CPS). 31 The team also identified that the time and familiarity that develops over the course of anticoagulation care creates a reciprocal relationship in which patients come to know their pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Staff develop a better understanding of the needs of both patients and patients' families and achieve what Radwin 23 and others 24,25 describe as "knowing your patient" (in our program, knowing patients and patients' families). This knowing has important implications for care delivery outcomes; the extent of knowing may contribute to the level of individualized care and the choice of how care is delivered.…”
Section: Benefits For Staffmentioning
confidence: 99%
“…Knowing the patient is a key concept within therapeutic decision making (Radwin, 1996), as with the ability to understand and treat the patient as an individual (O'Callaghan, 1995). This involves not only finding out the patient's perception and response to their situation, but the integration of knowledge surrounding specific treatments (Radwin, 1996).…”
Section: Commentarymentioning
confidence: 99%
“…This involves not only finding out the patient's perception and response to their situation, but the integration of knowledge surrounding specific treatments (Radwin, 1996). This reflective episode relates more to the clinical relationship and rapport with J, as opposed to knowing the patient as described by Jenny and Logan (1992), where time is considered to be essential in order to accumulate sufficient knowledge regarding the patient's current condition and concerns.…”
Section: Commentarymentioning
confidence: 99%